CUDA accelerated molecular surface generation. (15th August 2013) - D'Agostino, Daniele; Clematis, Andrea; Decherchi, Sergio; Rocchia, Walter; Milanesi, Luciano; Merelli, Ivan; Merelli, Ivan; Pérez‐Sánchez, Horacio; Gesing, Sandra
SUMMARY A proper and efficient representation of possibly complex and large molecular surfaces is an important task in bioinformatics and biophysics. Molecular surfaces indeed are used for different aims, in particular, for computation, as visual support tools for biologists, in electrostatics problems involving implicit solvents (e.g. while solving the Poisson–Boltzmann equation) or for molecular dynamics simulations. This is the reason why, in literature, a multitude of algorithms that differ on the basis of the adopted representation and the approach/technology used were proposed. In this paper we present a CUDA‐based software component able to produce high‐resolution molecular surfaces based on the Van der Waals, solvent accessible, Richards–Connolly and blobby definitions. The component was designed to be used in heterogeneous visualization pipelines; therefore, the representation of the molecular surfaces suits both the direct visualization and the efficient storing for following processing steps. Experimental results show speedup figures between 39.3 and 88.4 considering molecules of different sizes and surface resolutions, resulting in meshes of up to 258.6 million triangles. Copyright © 2013 John Wiley & Sons, Ltd.